Patients With Autoimmune Thyroiditis Present Similar Immunological Response to COVID-19 BNT162b2 mRNA Vaccine With Healthy Subjects, While Vaccination May Affect Thyroid Function: A Clinical Study - Paschou, Stavroula A.; Karalis, Vangelis; Psaltopoulou, Theodora; Vasileiou, Vasiliki; Charitaki, Ioanna; Bagratuni, Tina; Ktena, Vassiliki; Papandroulaki, Fotini; Gumeni, Sentiljana; Kassi, Georgia N.; Trougakos, Ioannis P.; Terpos, Evangelos; et al. (Frontiers in Endocrinology, 2022)
Background. This is the first study, that aimed: a) to compare immune response, namely the kinetics of neutralizing antibodies (Nabs), after vaccination with BNT162b2 mRNA vaccine between patients with autoimmune thyroiditis and controls, and b) to investigate changes in thyroid function in healthy subjects with no history of thyroid dysfunction before and after vaccination with BNT162b2 mRNA vaccine. Methods. The entire study consisted of two sub-studies. In the first sub-study, NAbs levels after BNT162b2 mRNA vaccination were compared between 56 patients with autoimmune thyroiditis and 56 age and gender-matched healthy controls from the day of the first dose until a period of up to three months after the second dose. In the second sub-study, thyroid hormones (T3, T4, TSH) and thyroid auto-antibodies levels (anti-TG, anti-TPO) of 72 healthy subjects with no history of thyroid disease were examined before (D1) and one month after completion of the second dose (D50). Results. Among patients with autoimmune thyroiditis, the median neutralizing inhibition on D22, immediately before second dose, was 62.5%. One month later (D50), values increased to 96.7%, while three months after the second dose NAbs titers remained almost the same (94.5%). In the healthy group, median NAbs levels at D22 were 53.6%. On D50 the median inhibition values increased to 95.1%, while after three months they were 89.2%. The statistical analysis did not show significant differences between two groups (p-values 0.164, 0.390, 0.105 for D22, D50 and three months). Regarding changes in thyroid function, the mean value for T4 before vaccination was 89.797 nmol/L and one month after the second dose was 89.11 nmol/L (p-value=0.649). On D1 the mean T3 value was 1.464 nmol/L, which dropped to 1.389 nmol/L on D50 (p-value = 0.004). For TSH, mean levels were 2.064 mIU/ml on D1 and fell to 1.840 mIU/ml one month after the second dose (p-value=0.037). Despite decrease, all thyroid hormone levels remained within the normal range. No changes were found for anti-TPO or anti-TG. Conclusions. This study provided evidence that patients with autoimmune thyroiditis present similar immunological response to COVID-19 BNT162b2 mRNA vaccine with healthy subjects, while vaccination may affect thyroid function.